PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA SISWA KELAS V UPT SPF SD NEGERI MANNURUKI KOTA MAKASSAR - Dwi Permata Sari; Abdul Azis; Try Gustaf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of fifth-grade students at the SPF Unit of Mannuruki Public Elementary School, Makassar City, in Pancasila Education. The research method used was quantitative with a one-group pretest-posttest design. The sample was all 32 fifth-grade B students. Data collection techniques included observation, testing, and documentation. Data were analyzed using quantitative descriptive analysis and inferential analysis using the t-test. This study aimed to determine the effect of the Discovery Learning model on improving student learning outcomes. The results showed that implementing the Discovery Learning model improved student learning outcomes. The average student score increased from 40.53 in the pretest to 50.06 in the posttest. A statistical test using paired samples test yielded a significance value <0.000, indicating a significant difference between learning outcomes before and after the treatment. Therefore, it can be concluded that the Discovery Learning model significantly improved Pancasila Education learning outcomes for fifth-grade B students at the SPF Unit of Mannuruki Public Elementary School, Makassar City.